Marine ecotourism for small pelagics as a source of alternative income generating activities to fisheries in a tropical community. (September 2021) - Cusack, Christopher; Sethi, Suresh A.; Rice, Aaron N.; Warren, Joseph D.; Fujita, Rod; Ingles, Jose; Flores, Jimely; Garchitorena, Edwina; Mesa, Sheryll V.
Abstract: Widespread overharvest has led to marine ecosystem degradation and declining fishery catches in many tropical communities. To allow stocks to recover and provide increased flows of food and income, reductions in fishing effort are necessary. The development of Alternative Income Generating Activities can help to reduce the economic reliance of coastal communities on fishing, potentially reducing pressure on fish stocks. Here we assess the local conditions which have enabled the creation of Alternative Income Generating Activities to fishing based on marine ecotourism in Moalboal, Philippines. Importantly, while marine ecotourism typically centers around charismatic megafauna, a combination of nearshore fringing reefs, the establishment of nearshore marine protected areas and the occurrence of a consistently large herring aggregation provide a large tourism draw to this community. Using a combination of regional and local economic statistics and stakeholder surveys, we implement an economic valuation of Moalboal marine ecotourism for 2018 and compare this valuation to an independent estimate of the extractive value of the herring aggregation. The Moalboal case indicates that a combination of strong community engagement in the governance of the ecotourism resource, a network of locally managed marine protected areas and the retention and distribution of economic benefits within the local community have led to a significant marine ecotourism sector. We contextualize these conditions into a set of potential enabling conditions for marine ecotourism as an Alternative Income Generating Activity to fishing to contribute insights to diversifying livelihood opportunities beyond extractive fishing for coastal communities in the tropics. Highlights: Ecotourism can provide alternative income generating activities for fishers. Marine reserves protect nearshore reefs and support ecotourism in Moalboal. Ecotourism value of tropical herring inside a reserve far outweighs harvest value. Key enabling conditions for community-based marine ecotourism are identified.